Ocean I3. Pedagogical Innovation for Sustainability - Itziar Rekalde-Rodríguez; Julieta Barrenechea; Yannick Hernandez (MDPI AG, 2021)
Universities are undertaking transformation projects that align their work with the Sustainable Development Goals. This paper describes how Ocean I3, an educational innovation project that aims to reduce plastic in the sea, has made an impact on its community over its three editions (2018/19 to 2020/21). Methodologically, it has been approached by the people who make up the technical team and academic coordination as an exploratory study using discrete, non-reactive techniques, mainly from the public domain (websites, blogs, press releases, etc.), and instruments, such as field notes and work material to manage, organize, and train within the project. The analytical procedure has represented a dynamic and systematic process of categorisation. The results highlight the repercussion of the project in terms of capstone projects, master's thesis, coursework, etc., produced by the students involved; association with employability; collaborative work from the teaching teams; monitoring experience for research purposes, and social dissemination of the project. It concludes by suggesting lines for Ocean I3 to work on in the future to make its footprint sustainable in institutions over time.